Bioethics versus medical law. - Villanueva Cañadas, Enrique (Medicina e Morale, 1998)
This article is a study on problems concerning medicine. It maintains that these problems have been solved through religious morals and ethics codes. History confirms this statement and also affirms that the philosophical reflection in medicine and the emergence of moral problems therein have necessarily led to the birth of bioethics. The author considers that one of the main duties of ethics is the "protection of man and of the citizen" in a world of constant evolution that is threatened by science and by the state. The physician is offered several points of reference in the area of law and ethics in order to deal with problems relating to ethics that emerge in clinical practice: the law, ethical codes, the Charter of the rights of the sick, the Charter of human rights, etc.. But in the end, the physician is alone with his conscience and he has to decide himself, and apparently sometimes there are conflicts between ethical norms and pratical situations. Therefore, by following a historical perspective, the article aims to examine the relationship between medical law and bioethics.